How ten speech-language pathologists provide informational counseling across the rehabilitation continuum for care partners of stroke survivors with aphasia. Issue 5 (4th May 2023) - Shafer, Jennifer S.; Haley, Katarina L.; Jacks, Adam
ABSTRACT: Background: Care partners are an integral part of the recovery process for people with aphasia after stroke, and they often depend on speech-language pathologists (SLPs) to provide the education, support, and training that care partners need across the recovery continuum. However, it is not clear how SLPs provide informational counseling across the recovery continuum or how they choose the type, quantity, and timing of the information they share with care partners. Aims: The aims of this study were to (1) identify what informational support speech-language pathologists currently provide to care partners of people with aphasia at each phase of the recovery continuum and (2) ascertain the perceived barriers/facilitators to providing tailored informational supports. Methods and Procedures: Ten practicing SLPs working with people with aphasia across various settings participated in individual semi-structured interviews. The interviews were audio-recorded, transcribed, and analysed using open-coding methods. Outcomes and Results: We delineate our results by each phase of the recovery continuum, from acute care to long-term life with aphasia. We discuss how SLPs apply their own judgment and experience in sharing information, how they supplement informational gaps, prepare care partners for assuming the caregiving role, and how they address care partner communicative, informational, and psychological needs once the person with aphasia returns home. We also discuss perceived barriers to providing timely care partner information. Conclusions: Our study supports and builds upon previous care partner work, , specifically, how SLPs integrate care partners into aphasia rehabilitation. SLPs are working to provide aphasia education in sometimes suboptimal circumstances. Across all phases of recovery, SLPs were hindered by lack of time and resources. Additional study is needed to determine how best to provide information to care partners, especially those who are not able to be present for treatment sessions.